International financial markets : prices and policies - Levich, Richard M. (Boston, Mass : Irwin/McGraw-Hill, 1998)
International financial markets; Foreign exchange markets; Offshore financial markets; Derivative security markets; International asset portfolios; International Asset portfolios; Financial risk management; Regulatory issues.
Keywords: Finance; Investment; International finance; Security markets; Securities; Foreign exchange; International finance; Investments, Foreign; Securities -- Prices